Dose related proliferative changes in the prostate of rats induced by eurycoma longifolia Jack (Tongkat Ali) extract - Faisal, Ghasak Ghazi; Ezzat Mustafa, Basma; Mustafa, Nazih Shaban; Najmuldeen, Ghazi Faisal (2014)
Eurycoma longifolia jack(E.L) root extract has become famous for giving enhanced sexual performance ability through elevation of serum testosterone levels in males. However, although very widely used, it’s possible adverse effects are poorly studied .The objective of this study is to find out if there are any pathological changes that occur in the prostate of rats due to consumption of E.L. root extract. Methodology:45 male rats where used in this study , they were divided into three groups ,group(A) contain 5 rats that represent the control group who did not receive any treatment, group (B) with 20 rats ,received 5mg/Kg twice daily of 100:1 freeze dried water extract of Eurycoma longifolia Jack roots and group (C) with 20 rats received 10mg/kg body weight twice daily of the same extract .The duration of treatment for both groups was 4 weeks. At the end of the experiment, blood was obtained from the rats and serum testosterone level (T) was analyzed. The rats were then terminated and the prostate was removed, weighed and its dimensions measured, then it was processed into haematoxiline and eosin stained slides which were observed under light microscope. Results: Group C showed a significant increase in prostate size, weight and serum T. Histopathological examination of the specimens revealed that there were no significant observable changes in group B in comparison with the control group while group C showed a marked cell proliferation of the prostatic gland lining epithelium that appeared as stratification and intraglandular villus formation of the usual single layer columnar epithelium. Areas of mild dysplastic changes were observed in the lining epithelium characterized by nuclear enlargement and irregularities in the nuclear membrane and hyperchromatism. These dysplastic changes were equivalent to low grade prostatic intraepithelial neoplasia PIN. Conclusion: E.L. root extract can cause abnormal proliferation in the prostatic epithelium and these changes are dose dependant.